(untitled) (PANGEEA, 2025)
ABSTRACT: In order to prepare the cadastral technical documentation for land registration, several stages must be completed. This documentation is set up after field measurements have taken place, after data has been processed and the cadastral plan related to a cadastral sector from a territorial administrative unit (LAU) has been obtained.